Monitoring of Partial Discharges in Cable Insulation and Cable Head Using Acoustic Method - RANACHOWSKI, Zbigniew; WIECZOREK, Krzysztof; RANACHOWSKI, Przemysław; DEBOWSKI, Tomasz (Archives of Acoustics, 2022)
The article presents the application of Acoustic Emission (AE) method for detection and registration of partial discharges (PD) generated in medium voltage (MV) cable isolation and MV cable head. The insulation of the high voltage cable is made of a flexible material whose properties are characterised by a high coefficient of attenuation of the acoustic signals. For this reason, the AE method has not been used so far to detect PD in energetic cables. The subjects of the research were the MV cable and the standard T-type cable head. The cable contained defects which were the source of partial discharges. In case of cable head the PD were provoked by thin grounded electrode which was introduced into connector opening. The results of AE measurements are presented in the form of spectrograms. Acoustic Emission was evoked when the applied voltage level reached the value of 7.5 kV for the cable and 4 kV for the cable head. The authors used the acoustic instrumentation of their own design intended for future field use. Obtaining successful results of partial discharges measurements using the acoustic method in the cable insulation makes an original contribution of the presented work.